Computed tomography dosimetry with high‐resolution detectors commonly used in radiotherapy — an energy dependence study. (8th September 2015) - Liebmann, Mario; Poppe, Bjoern; von Boetticher, Heiner
Abstract : New methods of dosimetry in computed tomography (CT) X‐ray fields require the use of high‐resolution detectors instead of pencil‐type ionization chambers typically used for CT dose index (CTDI) measurements. This paper presents a study on the suitability of a wide range of ionization chambers, diodes, and a two‐dimensional detector array, used primarily in radiation therapy, for CT and cone‐beam CT dosimetry. Specifically, the energy dependence of these detectors from 50 kVp up to 125 kVp is reported. All measurements were performed in reference to a calibrated diode for use in this energy region. The radiation quality correction factors provided by the manufacturer were used, depending on the measured half‐value layer (HVL) for the particular X‐ray beam. Our study demonstrated the general usability of thimble ionization chambers. These thimble ionization chambers showed a maximum variation in energy response of 5%. Ionization chambers with even smaller sensitive volume, and which exhibit similar variation in energy dependence, can be used if higher spatial resolution is required. Furthermore, the investigated detectors are better suited for dosimetry at CT and CBCT units than conventional large volume or flat detectors, due to their rotational symmetry. Nevertheless, a flat detector can be used for certain measurement tasks, such as the acquisition of percent depth‐dose curves or beam profiles for nonrotating beams, which are important for beam characterization. PACS numbers: 87.57.uq, 87.56.Da, 87.57.Q‐